La palabra en la piedra / Tomás Meabe ; prólogo de José Luis Rodríguez Zapatero ; Juan María Calles, selección y edición - Rodríguez Zapatero, José Luis (1960-) Calles, Juan María; Meabe, Tomás (1879-1915)
Bibliografía: p. 63-64